MXene / MWCNT reinforced charcoal-based composite phase change material and preparation method thereof
By adding MWCNT and MXene to biochar-based composite PCM, the problem of insufficient thermal conductivity and photothermal conversion capabilities is solved, and significant improvements in thermal conductivity and photothermal conversion capabilities are achieved, and its application scenarios are expanded.
Patent Information
- Application Number
- CN202411800103.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The thermal conductivity and photothermal conversion ability of biochar-based composite PCM are poor, which limits its wide application in many fields.
By adding thermal conductivity and photothermal conversion enhancement material MWCNT and photothermal conversion enhancement material MXene to biochar-based composite PCM, its thermal conductivity and photothermal conversion capabilities are improved. Specific steps include preparing MWCNT and MXene suspensions blended with biochar and preparing enhanced composite PCM by vacuum impregnation.
The thermal conductivity and photothermal conversion capacity of composite PCM were significantly improved. Compared with paraffin and unenhanced composite PCM, the thermal conductivity was increased by 313.77% and 26.3%, respectively, and the photothermal conversion capacity was also significantly enhanced.
Smart Images

Figure CN119614158A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change materials, and in particular to a MXene / MWCNT-enhanced biochar-based composite phase change material and a preparation method thereof. Background Art
[0002] At present, the rapid development of the global economy has driven the fossil energy crisis and the increase of greenhouse gas emissions. The worsening environmental problems will eventually threaten the sustainable development of the world. Statistics show that the global energy demand will reach 556.63 trillion kilojoules in 2020, and it is expected that this figure may grow to 820 trillion kilojoules by 2040. Although the utilization rate of clean energy has increased with the development of renewable energy in recent years, by 2040, traditional energy (such as natural gas) will still account for more than 76% of energy demand. Serious energy problems are undoubtedly promoting the development of renewable energy and clean energy. However, the stability of renewable energy such as solar energy and wind energy is a key factor limiting their widespread application. Therefore, more and more researchers have begun to explore the conversion and storage of clean energy to improve energy stability and solve the problem of asynchronous energy supply and demand. This method can more effectively utilize renewable energy, reduce dependence on fossil energy, promote the transformation of the energy system, and accelerate the realization of carbon neutrality goals.
[0003] Current heat storage technologies mainly include sensible heat storage, chemical heat storage, phase change heat storage and electrochemical heat storage. Among them, phase change heat storage technology occupies an important position in the field of heat storage due to its safety, stability and large heat storage capacity. Phase change heat storage mainly relies on the solid-liquid phase change process of phase change material (PCM) to achieve energy conversion by absorbing or releasing a large amount of latent heat, thereby alleviating the problem of imbalance between supply and demand of clean energy. However, in liquid state, PCM has a serious leakage risk, which will not only cause the failure of the heat storage system, but may even cause major industrial safety problems. In addition, most PCMs have poor thermal conductivity, making it difficult to quickly transfer and absorb heat, resulting in significant heat loss. These problems have limited the engineering application of solid-liquid phase change PCM to a certain extent. In order to solve these problems, composite PCM came into being. Composite PCM encapsulates PCM through encapsulation materials, effectively solving its leakage problem. At the same time, the thermal conductivity and photothermal conversion capacity of composite PCM can be improved by rationally utilizing the characteristics of encapsulation materials or adding appropriate amounts of enhancers.
[0004] Porous materials are ideal for storing PCM due to their good pore structure and large specific surface area, including carbonaceous materials such as biochar, graphene and carbon nanotubes. These materials have been widely used in the field of composite PCM to solve the problems of PCM leakage and insufficient thermal performance. In terms of the treatment of waste biomass, many industries still use traditional methods of incineration or landfill. However, these methods not only waste biomass energy, but also bring serious environmental pollution. With the proposal of environmental protection goals such as carbon neutrality, the recycling of waste biomass has become an issue that cannot be ignored. Waste biomass can be pyrolyzed under specific conditions to prepare biochar with good pore structure and large specific surface area, which is an environmentally friendly carbon material. As a carbon material, biochar usually has good adsorption capacity and high thermal conductivity. In addition, due to its black appearance, biochar has strong light absorption and photothermal conversion capabilities. Therefore, biochar has been widely used as an encapsulation material in composite PCM research. Studies have shown that the use of biochar prepared from biomass for the storage of solid-liquid phase change PCM not only realizes waste utilization, but also effectively solves the problem of PCM leakage.
[0005] The development of biochar-based composite PCM provides an effective way to utilize biomass and solid-liquid PCM. Although biochar, as a product of high-value utilization of biomass, has good thermal conductivity and adsorption, its thermal conductivity and pore properties are still somewhat different from those of industrial carbon materials such as expanded graphite and carbon multi-walled nanotubes (MWCNT), which limits its wide application in many fields. However, the large-scale use of industrial carbon materials will inevitably bring about environmental pollution, which is contrary to the concept of energy conservation, environmental protection and carbon neutrality.
[0006] For example, the patent with publication number CN116410530A discloses a high thermal conductivity carbon nanotube composite masterbatch and a preparation method thereof, which simply synthesizes a leak-free composite PCM and ignores the photothermal conversion capability and thermal conductivity.
[0007] For example, the patent with publication number CN107603571A discloses the preparation of shaped expanded graphite-based erythritol medium-temperature composite phase change heat storage materials. The use of industrial carbon materials brings certain pollution, and the composite PCM prepared from biochar has been continuously narrowing the gap with it under reasonable treatment.
[0008] For example, the journal Enhancing the light-thermal absorption and conversion capacity of diatom-based biomass / polyethylene glycol composites phase change material by introducing MXene uses MXene as an "enhancer" for light-thermal absorption and conversion to prepare a new type of shape-stable phase change material, but does not focus on the optimization of thermal conductivity, which has certain limitations.
[0009] For example, the patent with publication number CN109777368A discloses a porous carbon composite phase change material and its preparation method, which uses a graphene-type coating to enhance the thermal conductivity of the porous carbon skeleton. The graphene-type coating in the patent is attached by soaking and drying. The coating obtained by this method only covers the surface of the carbon skeleton, and problems such as coating failure will inevitably occur during the application process, and a stable enhancement effect cannot be formed.
[0010] For example, the patent with publication number CN116536032A discloses a composition for preparing a high thermal conductivity composite phase change material, a high thermal conductivity composite phase change material, and a preparation method and application thereof. The patent has complicated preparation steps and uses a large amount of chemical reagents in the treatment process, which causes serious pollution to the environment. In addition, the high-temperature graphitization and precise chemical modification process may be difficult to maintain consistency in large-scale production, so it is difficult to obtain large-scale application. Summary of the invention
[0011] Technical Problems Solved by the Invention
[0012] The present invention is used to solve the problem of poor thermal conductivity and poor photothermal conversion capacity of biochar-based composite PCM. Based on this, the present invention successfully enhances the thermal properties (photothermal conversion capacity and thermal conductivity) of biochar-based composite PCM while ensuring the utilization of waste biomass, realizes the expansion of the use scenarios of biochar-based composite PCM, and improves the competitiveness of clean support materials in the field of composite PCM.
[0013] Technical solution adopted by the present invention
[0014] The present invention uses oleophobic biochar as the basic support skeleton and adds a small amount of reinforcing materials (thermal conductivity reinforcing material MWCNT, photothermal conversion reinforcing material MXene) to enhance the thermal properties of biochar-based composite PCM, including thermal conductivity and photothermal conversion capabilities.
[0015] To expand on this, it means:
[0016] First, the present invention provides a method for preparing a MXene / MWCNT enhanced biochar-based composite phase change material, comprising the following steps:
[0017] S1 MWCNT and metal salt are used to prepare a suspension; biomass is added to the suspension, and the mixture is dried to obtain a precursor;
[0018] S2 heat-treats the precursor to obtain biochar; the biochar is mixed with a perfluorooctanoic acid ethanol solution and dried to obtain a support material;
[0019] S3: blending and drying the support material and the MXene solution to obtain a reinforced support material;
[0020] The S4 enhanced support material was vacuum impregnated to obtain a bio-based composite phase change material.
[0021] According to some preferred embodiments, in S1, the ratio of MWCNT to metal salt is 1 g:30-100 ml, and the concentration of the metal salt is 1-3M.
[0022] According to some preferred embodiments, in S1, the mass ratio of MWCNT to biomass is 1:0.05-0.2.
[0023] According to some preferred embodiments, in S1, the biomass includes at least one of wood materials, kitchen waste, and organic waste.
[0024] According to some preferred embodiments, in S1, the metal salt includes at least one of ZnCl2, CaCl2, FeCl3, FeCl2, Zn(NO3)2, Ca(NO3)2, and Fe(NO3)3.
[0025] According to some preferred embodiments, in S2, the heat treatment is carried out in a high temperature tube furnace at a rate of 3-6°C / min from 25°C to 500-700°C and maintained for 1-4h under a nitrogen atmosphere.
[0026] According to some preferred embodiments, in S2, the ratio of biochar to perfluorooctanoic acid ethanol solution is 1 g:10-20 ml, and the concentration of perfluorooctanoic acid ethanol solution is 0.01-0.05 mol / L.
[0027] According to some preferred embodiments, in S2, the biochar and the perfluorooctanoic acid ethanol solution are shaken and mixed at room temperature for 36 to 60 hours, then rinsed with anhydrous ethanol, and then heated at 60 to 90° C. for 20 to 30 hours.
[0028] According to some preferred embodiments, in S3, the ratio of the support material to the MXene solution is 1 g: 2-10 mg / ml, and the concentration of the MXene solution is 3-8 mg / ml.
[0029] According to some preferred embodiments, in S3, the blending is performed by ultrasonic blending, and the mixture is dried at 85° C. until completely dried.
[0030] According to some preferred embodiments, in S3, the method for preparing MXene is to use Ti3AlC2 as a precursor, use a mixture of LiF and hydrochloric acid, and selectively etch the Al layer to prepare MXene nanosheets.
[0031] Specifically: 3.12g of LiF was mixed with 40ml of 9M hydrochloric acid solution and reacted at 40°C for 30min. 2.00g of Ti3AlC2 powder was slowly added and fully reacted at 500rpm and 40°C for 48h. After adding a small amount of 1M hydrochloric acid solution to the obtained suspension, centrifuged at 5000rmp for 5min, repeated 5 times, and then washed with 1M hydrochloric acid and LiCl solution. The washed sample was centrifuged at 3000rmp for 30min to obtain MXene precipitation and washed with deionized water until neutral. Take 0.5g of MXene powder and dissolve it in 30ml of deionized water, ultrasonically treat it for 30min, then centrifuge it at 3000rmp for 15min, take the supernatant, filter it with a 0.22μm water filter membrane, and remove the single-layer MXene material after drying.
[0032] In addition to the above-disclosed method for preparing MXene, those skilled in the art may also choose other methods for preparing MXene.
[0033] According to some preferred embodiments, in S4, the vacuum impregnation method is as follows: the reinforced support material is immersed in excess paraffin wax, and a vacuum environment is maintained at 50-70°C for 2-5 hours. After the impregnation is completed, the composite is placed in a constant temperature box and turned over at regular intervals to ensure gravity-free deposition until no molten paraffin wax seeps out, thereby obtaining a bio-based composite phase change material.
[0034] Second, the present invention provides a MXene / MWCNT-enhanced biochar-based composite phase change material obtained by the above-mentioned preparation method.
[0035] Beneficial effects achieved by the present invention
[0036] (1) The present invention uses biological waste as the source of biochar, thereby making high-value use of biomass and improving energy utilization efficiency; at the same time, it is more environmentally friendly and energy-saving than industrial products.
[0037] (2) The present invention completes the incorporation and activation of MWCNTs in a one-step method, and uses an immersion process to load MXene. Incorporating MWCNTs during the biomass activation process simplifies the processing steps and reduces the application conditions. During the immersion activation process, MWCNTs can fully contact the biomass and effectively adhere to the biomass. In the subsequent slow carbonization process, as the temperature rises and the organic matter decomposes, the biochar gradually forms a good connection with the MWCNTs, and a part of the MWCNTs enters the pores of the biochar. When heat is transferred to the composite material, these MWCNTs can form an effective thermal conductivity network to improve the thermal conductivity of the material. If MWCNTs are directly incorporated into the formed biochar, unstable connections may occur, and the MWCNTs are distributed on the surface of the biochar, and cannot efficiently form a thermal conductivity network, greatly reducing its thermal conductivity enhancement effect.
[0038] (3) The present invention optimizes the preparation process of the supporting material by incorporating MWCNT, thereby achieving the purpose of increasing the storage space of biochar. Based on this, one of the improvement methods is to select intact wood instead of crushed biomass, retain the water channels of the original wood biomass, and create a larger storage space, but at the same time, in order to achieve a stable connection between biochar and MWCNT, the activation and the incorporation of MWCNT are combined into one step. This is because, under normal circumstances, the application of biochar will use crushed biomass, add some additives after burning into carbon, and then load PCM for molding. This method mainly reduces the number of operating steps, and tableting will also cause certain difficulties in application.
[0039] (4) The composite PCM prepared by the present invention has a thermal conductivity increased by 313.77% and 26.3% compared with paraffin and unreinforced composite PCM, respectively. The enhancement of photothermal conversion capacity is reflected in two aspects: first, in the illumination experiment, the temperature change before and after the enhancement is 20.7°C different; second, in the absorbance test, in the main concentrated area of radiant energy (visible light, near infrared), the absorbance of the enhanced support material is 21.16% and 30.67% higher than that of the ordinary oleophobic material, respectively. The thermal conductivity and photothermal conversion capacity (radiation absorption capacity) are significantly enhanced.
[0040] (5) The composite PCM provided by the present invention uses a biochar-based support material, and its encapsulation efficiency of paraffin is further improved to 85.18%, which is already at the leading level in the industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Diagram of the device for testing samples on the photothermal conversion test bench.
[0042] Figure 2 This is the DSC image of the composite PCM and paraffin prepared in Example 1.
[0043] Figure 3 The temperature variation curves of the composite PCM prepared in Example 1 and Comparative Example 1 in the light-to-heat conversion capacity test are shown.
[0044] Figure 4 Infrared photos of the composite PCM prepared in Example 1 and Comparative Example 1 taken at different time points during the light-to-heat conversion capacity test.
[0045] Figure 5 The graph is a test result of the absorbance of the carbon material of Example 1 and Comparative Example 1 at different wavelengths;
[0046] Figure 6 is a SEM image of the enhanced support material of Example 1 (scale: 50 μm);
[0047] Figure 7 This is a SEM image of the reinforced support material of Example 1 (scale: 5 μm). DETAILED DESCRIPTION
[0048] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0049] Preparation of MXene:
[0050] Using Ti3AlC2 as a precursor, a mixture of LiF and hydrochloric acid was used to selectively etch the Al layer to prepare MXene nanosheets. 3.12g of LiF was mixed with 40ml of 9M hydrochloric acid solution and reacted at 40°C for 30min. 2.00g of Ti3AlC2 powder was slowly added and fully reacted at 500rpm and 40°C for 48h. After adding a small amount of 1M hydrochloric acid solution to the obtained suspension, centrifuged at 5000rmp for 5min, repeated 5 times, and then washed with 1M hydrochloric acid and LiCl solution. The washed sample was centrifuged at 3000rmp for 30min to obtain MXene precipitation and washed with deionized water until neutral. Take 0.5g of MXene powder and dissolve it in 30ml of deionized water, ultrasonically treat for 30min, then centrifuge at 3000rmp for 15min, take the supernatant, filter with a 0.22μm water filter membrane, and remove the single-layer MXene material after drying.
[0051] Example 1
[0052] MWCNT was mixed with 2M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain a MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried white pine waste at a ratio of 1:10 (wt%) of MWCNT to white pine waste, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0053] The incorporation method of MXene is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 5 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:5 ml, ultrasonically treated for 5 hours, and then completely dried in an 85°C drying oven to obtain a reinforced support material.
[0054] The composite PCM was prepared using a vacuum impregnation method. First, a beaker filled with excess liquid paraffin was placed in a vacuum drying oven at 60°C to keep the temperature stable. Then, the enhanced support material was placed in the beaker, and then the vacuum environment was maintained at 60°C for 3 hours. After the impregnation, the composite PCMs were taken out and placed on filter paper and placed in a 70°C constant temperature box. The filter paper was replaced every 15 minutes and the composite PCMs were turned over to ensure that there was no uneven distribution of PCMs due to gravity deposition, until there was no molten paraffin seeping out of the filter paper, and an enhanced and leak-free composite PCM was obtained.
[0055] Example 2
[0056] MWCNT was mixed with 3M ZnCl2 solution at a ratio of 1g:60ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain a MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried white pine waste at a ratio of 1:12 (wt%) of MWCNT to white pine waste, ultrasonicated for 3h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.03 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0057] The incorporation method of MXene is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 5 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:5 ml, ultrasonically treated for 5 hours, and then completely dried in an 85°C drying oven to obtain a reinforced support material.
[0058] The preparation of composite PCM is the same as in Example 1.
[0059] Example 3
[0060] MWCNT was mixed with 2M ZnCl2 solution at a ratio of 1g:40ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain a MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried white pine waste at a ratio of 1:10 (wt%) of MWCNT to white pine waste, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0061] The incorporation method of MXene is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 6 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g: 5 ml, ultrasonically treated for 5 hours, and then completely dried in an 85°C drying oven to obtain a reinforced support material.
[0062] The preparation of composite PCM is the same as in Example 1.
[0063] Example 4
[0064] MWCNT was mixed with 1.5M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain a MWCNT / ZnCl2 suspension. The suspension was mixed with washed and dried coffee grounds waste at a ratio of 1:20 (wt%) of MWCNT to coffee grounds waste, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0065] The incorporation method of MXene is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 5 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:5 ml, ultrasonically treated for 5 hours, and then completely dried in an 85°C drying oven to obtain a reinforced support material.
[0066] The preparation of composite PCM is the same as in Example 1.
[0067] Example 5
[0068] MWCNT was mixed with 2M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried corn stalks at a ratio of 1:7 (wt%) of MWCNT to corn stalks, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0069] The method of incorporating MXene is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 3 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:12 ml, ultrasonically treated for 4 hours, and then completely dried in an 85°C drying oven to obtain a reinforced support material.
[0070] The preparation of composite PCM is the same as in Example 1. After the composite PCM powder is obtained, a molding process is performed.
[0071] Example 6
[0072] MWCNT was mixed with 2M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried corn stalks at a ratio of 1:5 (wt%) of MWCNT to corn stalks, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0073] The method of MXene incorporation is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 3 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:15 ml, ultrasonically treated for 5 hours, and then completely dried in a drying oven at 85°C to obtain a reinforced support material.
[0074] The preparation of composite PCM is the same as in Example 1. After the composite PCM powder is obtained, a molding process is performed.
[0075] Example 7
[0076] MWCNT was mixed with 2M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried kitchen waste at a ratio of 1:15 (wt%) of MWCNT to kitchen waste, ultrasonicated for 2h and placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample is taken out, the biochar is mixed with 0.02mol / L perfluorooctanoic acid ethanol solution in a ratio of 1g:15ml, and mixed in an oscillator at 150r / min at room temperature for 48h, then rinsed twice with anhydrous ethanol, and dried at 75°C for 24h to finally obtain a support material with oleophobic properties and containing MWCNT. The MXene incorporation method is as follows. A single layer of MXene is mixed with deionized water and ultrasonically treated for 5min to obtain a 5mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1g:8ml, ultrasonically treated for 5h, and then completely dried in an 85°C drying oven to obtain an enhanced support material.
[0077] The preparation of composite PCM is the same as in Example 1. After the composite PCM powder is obtained, a molding process is performed.
[0078] Example 8
[0079] MWCNT was mixed with 1.5M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried kitchen waste at a ratio of 1:20 (wt%) of MWCNT to kitchen waste, ultrasonicated for 2h and then placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0080] The method of incorporating MXene is as follows: a monolayer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 6 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:10 ml, ultrasonically treated for 5 hours, and then completely dried in a drying oven at 85°C to obtain a reinforced support material.
[0081] The preparation of composite PCM is the same as in Example 1. After the composite PCM powder is obtained, a molding process is performed.
[0082] Example 9
[0083] MWCNT was mixed with 2M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain a MWCNT / ZnCl2 suspension. The suspension was mixed with cleaned and dried white pine waste at a ratio of 1:10 (wt%) of MWCNT to white pine waste, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0084] The incorporation method of MXene is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 3 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:6 ml, ultrasonically treated for 5 hours, and then completely dried in an 85°C drying oven to obtain a reinforced support material.
[0085] The preparation of composite PCM is the same as in Example 1.
[0086] Example 10
[0087] MWCNT was mixed with 2M ZnCl2 solution at a ratio of 1g:50ml, ultrasonicated for 30min and then allowed to stand for 5min, repeated 3 times to obtain a MWCNT / ZnCl2 suspension. The suspension was mixed with washed and dried waste coffee grounds at a ratio of 1:15 (wt%) of MWCNT to waste coffee grounds, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. The dried MWCNT / ZnCl2 / biomass mixture was heated from 25°C to 600°C at a rate of 5°C / min in a high-temperature tube furnace for 2h, then cooled naturally, and nitrogen was passed through at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02 mol / L perfluorooctanoic acid ethanol solution in a ratio of 1 g:15 ml, and mixed in an oscillator at 150 r / min at room temperature for 48 hours, then rinsed twice with anhydrous ethanol and dried at 75°C for 24 hours, finally obtaining a support material with oleophobic properties and containing MWCNTs.
[0088] The MXene incorporation method is as follows: a single layer of MXene is mixed with deionized water and ultrasonically treated for 5 minutes to obtain a 6 mg / ml MXene solution with good dispersion. Subsequently, the biochar and MXene dispersion are mixed in a ratio of 1 g:3 ml, ultrasonically treated for 5 hours, and then completely dried in a drying oven at 85°C to obtain a reinforced support material.
[0089] The preparation of composite PCM is the same as in Example 1. After the composite PCM powder is obtained, a molding process is performed.
[0090] Comparative Example 1
[0091] The cleaned and dried white pine waste was soaked in a 2mol / L ZnCl2 solution for 24 hours, filtered and placed in a 65°C drying oven for dehydration for 24 hours until completely dry. After drying, the ZnCl2 / biomass mixture was heated from 25°C to 600°C in a high-temperature tube furnace at a rate of 5°C / min for 2 hours, then cooled naturally, and nitrogen was introduced at 200mL / min during the period. After the sample was taken out, the biochar was mixed with 0.02mol / L perfluorooctanoic acid ethanol solution at a ratio of 1g:15ml, and mixed at room temperature in an oscillator at 150r / min for 48 hours, then rinsed twice with anhydrous ethanol, and dried at 75°C for 24 hours, finally obtaining biochar with oleophobic properties.
[0092] The composite PCM was prepared using a vacuum impregnation method. First, a beaker filled with excess liquid paraffin was placed in a vacuum drying oven at 60°C to keep the temperature stable. Then, oleophobic biochar was placed in the beaker, and then the vacuum environment was maintained at 60°C for 3 hours. After the impregnation, the composite PCMs were taken out and placed on filter paper and placed in a 70°C constant temperature box. The filter paper was replaced every 15 minutes and the composite PCMs were turned over to ensure that there was no uneven distribution of PCMs due to gravity deposition, until there was no molten paraffin seeping out of the filter paper, and a leak-free composite PCM was obtained.
[0093] Comparative Example 2
[0094] The process of preparing oleophobic biochar is the same as that of Comparative Example 1.
[0095] MWCNT was mixed with deionized water at a ratio of 1g:50ml, ultrasonicated for 30min, and then allowed to stand for 5min, repeated 3 times to obtain a MWCNT suspension. The suspension was mixed with oleophobic biochar at a ratio of 1:10 (wt%) of MWCNT to oleophobic biochar, ultrasonicated for 2h, placed in an oscillator, mixed and oscillated for 24h, then filtered and completely dried in an oven at 80°C. A monolayer MXene was mixed with deionized water and ultrasonicated for 5min to obtain a 5mg / ml MXene solution with good dispersion. Subsequently, the oleophobic biochar / MWCNT mixture was mixed with the MXene dispersion at a ratio of 1g:5ml, ultrasonicated for 5h, and then completely dried in an 85°C drying oven to obtain an enhanced biochar that is easy to incorporate and surface-loaded.
[0096] Test example
[0097] Through Figure 1 The temperature change of the sample under the irradiation of a certain simulated light source in the photothermal conversion test bench shown reflects the photothermal conversion ability of the sample, and the thermal conductivity of the sample is characterized by a HotDisk thermal conductivity meter. The results are shown in Table 1.
[0098] Table 1
[0099]
[0100] Figure 2 This is the DSC image of the composite PCM and paraffin prepared in Example 1.
[0101] Figure 3 The temperature variation curves of the composite PCM prepared in Example 1 and Comparative Example 1 in the light-to-heat conversion capacity test are shown.
[0102] Figure 4 Infrared photos of the composite PCM prepared in Example 1 and Comparative Example 1 taken at different time points during the light-to-heat conversion capacity test.
[0103] Figure 5 Graph showing the absorbance test results of the carbon material of Example 1 and Comparative Example 1 at different wavelengths.
[0104] Table 2 shows the thermal parameters of paraffin and the composite PCM prepared in Example 1.
[0105] Table 2
[0106]
[0107] The formula for calculating the encapsulation efficiency is:
[0108]
[0109] Among them, H M,PW and H F,PW is the melting enthalpy and crystallization enthalpy of paraffin, H M,PW / BC-MM With H F,PW / BC-MM are the melting enthalpy and crystallization enthalpy of Example 1.
[0110] The calculation formula of encapsulation efficiency is referenced from: The preparation of a green shape-stabilized composite phase change material of polyethylene glycol / SiO2 with enhanced thermal performance based on oil shale ash via temperature-assisted sol-gel method.
[0111] At the same time, the encapsulation rates of other types of phase change materials are listed here, as shown in Table 3.
[0112] Table 3
[0113]
[0114] A: A novel form-stable phase change material of palmitic acid-carbonized pepper straw for thermal energy storage.
[0115] B:Porous biochar / heptadecane composite phase change material withleak-proof,high thermal energy storage capacity and enhanced thermalconductivity.
[0116] C: Water evaporation inspired biomass-based PCM from daisy stem and paraffin for building temperature regulation.
[0117] D:Capric-stearic acid mixture impregnated carbonized waste sugar beetpulp as leak-resistive composite phase change material with effective thermalconductivity and thermal energy storage performance.
[0118] The surface morphology of the reinforced support material prepared in Example 1 was observed. Figure 6 and Figure 7 shown.
[0119] Depend on Figure 6-Figure 7 It can be seen that in addition to the large amount of MXene covering the surface, Figure 7 The pores of biochar contain a large number of MWCNTs, which cannot be achieved by surface blending.
Claims
1. A method for preparing a MXene / MWCNT-enhanced biochar-based composite phase change material, characterized in that: The steps include: S1 MWCNT and metal salt are used to prepare a suspension; biomass is added to the suspension, and the mixture is dried to obtain a precursor; S2 heat-treats the precursor to obtain biochar; The biochar and the perfluorooctanoic acid ethanol solution are mixed and dried to obtain a support material; S3: blending and drying the support material and the MXene solution to obtain a reinforced support material; The S4 enhanced support material was vacuum impregnated to obtain a bio-based composite phase change material.
2. The method for preparing the MXene / MWCNT enhanced biochar-based composite phase change material according to claim 1, characterized in that: S2 includes features (S2-1): (S2-1) Heat treatment: in a high temperature tube furnace, the temperature is raised from 25°C to 500-700°C at a rate of 3-6°C / min and maintained for 1-4 hours in a nitrogen atmosphere.
3. The method for preparing the MXene / MWCNT enhanced biochar-based composite phase change material according to claim 1, characterized in that: S2 includes at least one of features (S2-2) to (S2-3): (S2-2) the ratio of biochar to perfluorooctanoic acid ethanol solution is 1 g: 10-20 ml, and the concentration of perfluorooctanoic acid ethanol solution is 0.01-0.05 mol / L; (S2-3) The biochar and perfluorooctanoic acid ethanol solution were mixed by shaking at room temperature for 36 to 60 hours, then rinsed with anhydrous ethanol and then heated at 60 to 90°C for 20 to 30 hours.
4. The method for preparing the MXene / MWCNT enhanced biochar-based composite phase change material according to claim 1, characterized in that: S3 includes at least one of the features (S3-1) to (S3-2): (S3-1) The ratio of support material to MXene solution is 1 g: 2 to 10 mg / ml, and the concentration of MXene solution is 3 to 8 mg / ml; (S3-2) Ultrasonic blending is adopted for blending, and drying is carried out at 85° C. until it is completely dry.
5. The method for preparing the MXene / MWCNT enhanced biochar-based composite phase change material according to claim 1, characterized in that: S3 includes features (S3-3): (S3-3) The preparation method of MXene is to use Ti3AlC2 as a precursor, use a mixture of LiF and hydrochloric acid, and selectively etch the Al layer to prepare MXene nanosheets.
6. The method for preparing the MXene / MWCNT enhanced biochar-based composite phase change material according to claim 1, characterized in that: In S4, vacuum impregnation method: immerse the reinforced support material in excess paraffin wax, maintain a vacuum environment at 50-70°C for 2-5 hours, and after the impregnation, place the composite in a constant temperature box and turn it over at regular intervals to ensure gravity-free deposition until no molten paraffin wax seeps out, thereby obtaining a bio-based composite phase change material.
7. The method for preparing the MXene / MWCNT enhanced biochar-based composite phase change material according to any one of claims 1 to 6, characterized in that: S1 includes at least one of features (S1-1) to (S1-2): (S1-1) The ratio of MWCNT to metal salt is 1 g:30-100 ml, and the concentration of metal salt is 1-3 M; (S1-2) The mass ratio of MWCNT to biomass is 1:0.05~0.
2.
8. The method for preparing the MXene / MWCNT enhanced biochar-based composite phase change material according to claim 7, characterized in that: S1 includes at least one of features (S1-3) to (S1-4): (S1-3) the biomass includes at least one of wood materials, kitchen waste, and organic waste; (S1-4) The metal salt includes at least one of ZnCl2, CaCl2, FeCl3, FeCl2, Zn(NO3)2, Ca(NO3)2, and Fe(NO3)3.
9. A MXene / MWCNT-enhanced biochar-based composite phase change material obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation of molded expanded graphite-based erythritol medium-temperature composite phase change heat storage material
CN107603571A
Porous carbon composite phase changing material and preparation method thereof
CN109777368A
High-thermal-conductivity carbon nanotube composite master batch and preparation method thereof
CN116410530A
Composition for preparing high-thermal-conductivity composite phase change material, high-thermal-conductivity composite phase change material as well as preparation method and application of high-thermal-conductivity composite phase change material
CN116536032A
Heat storage composite phase change material based on pitaya peel derived porous carbon as well as preparation method and application of heat storage composite phase change material
CN116948606A